Fungsi Pajak Terhadap Lingkungan Hidup - Sugiharti, Dewi Kania; Hartanto, Ghani Satria; Indri Yuliafitri; Ismail, Shafinar (Magister of Law, Faculty of Law, University of Mataram, 2025)
The environment is an integral part of human life, as it provides essential resources, including food, water, and other necessities. It is the primary source for meeting our various needs. However, many activities that claim to improve welfare and promote economic development actually cause environmental destruction, such as forest burning, illegal logging, and the exploitation of natural resources with no regard for environmental concerns. Government-led development projects require substantial funding. Funding for such projects comes from government savings, which are taxes. Taxes are a highly reliable source of revenue for the Indonesian government at both the central and local levels. Taxes are closely related to development and the environment, so studying this issue in depth is important because it has theoretical and practical value in developing environmentally sustainable practices for a just and prosperous Indonesia. This research focuses on the gap between Indonesian tax regulations, which have not yet significantly accommodated environmental conservation interests. Tax collection in Indonesia is primarily focused on fulfilling the State Budget (APBN). This research analyses the tax law system to determine how it can accommodate the government’s financial interests while also providing space for environmental protection and not hindering the community’s ability to strive for a decent and prosperous life. This descriptive-analytical research uses a normative legal approach. The research stages include a literature review and fieldwork. Data collection techniques were carried out through document studies. Conclusions and research results were drawn using qualitative normative analysis methods.